The essence of love in Kierkegaard. Interpretation of Works of love (1847) - Torralba, Francesc (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The goal of this article is to explore the notion of love present in Søren Kierkegaard's The works of Love. For several reasons, this work has been ignored among the critical commentators of Kierkegaard. The author clarifies the foundations, the qualities and the expressions of the love according to Søren Kierkegaard's philosophy.
Keywords: love; God; eternity